Identification of the Infection Source of an Outbreak of Mycobacterium Chelonae Keratitis After Laser in Situ Keratomileusis. Issue 1 (January 2018) - Nascimento, Heloisa; Viana-Niero, Cristina; Nogueira, Christiane Lourenço; Martins Bispo, Paulo José; Pinto, Fernando; de Paula Pereira Uzam, Camila; Matsumoto, Cristianne Kayoko; Oliveira Machado, Antônia Maria; Leão, Sylvia Cardoso; Höfling-Lima, Ana Luisa; de Freitas, Denise
Abstract : Purpose: Nontuberculous mycobacteria keratitis is a rare but challenging complication of laser in situ keratomileusis (LASIK). This study was conducted to determine the source(s) of infection in a cluster of cases of keratitis after LASIK and to describe this outbreak and patients' outcomes. Methods: In this retrospective, case series, single-center study, 86 patients were included who underwent LASIK or photorefractive keratectomy between December 2011 and February 2012. Corneal scrapes from the affected eyes, samples of tap and distilled water, water from the reservoir of the distilling equipment, steamer, and autoclave cassette; antiseptic and anesthetic solutions and surgical instrument imprints were cultivated in liquid and on solid media. Gram-negative bacteria and yeasts were identified using automated systems and mycobacteria by polymerase chain reaction–restriction enzyme analysis of the hsp65 gene (PRA- hsp65 ) and DNA sequencing. Mycobacterial isolates were typed by pulsed-field gel electrophoresis. The cases and outcomes are described. The main outcome measure was identification of the source(s) of the mycobacterial infections. Results: Eight (15 eyes) of 86 patients (172 eyes) who underwent LASIK developed infections postoperatively; no patients who underwent photorefractive keratectomy developed infections. Mycobacterium chelonae was isolated from 4 eyes. The distilled water collected in the surgical facility contained the same M. chelonae strain isolated from the patients' eyes. Different gram-negative bacteria and yeasts were isolated from samples collected at the clinic but not from the patients' eyes. Conclusions: Tap water distilled locally in surgical facilities may be a source of infection after ocular surgery and its use should be avoided. Abstract : Supplemental Digital Content is Available in the Text.